Study of effect of serum magnesium concentration on clinical outcome of critically sick patients in medical intensive care unit - Kumari, Ganedi S. (International Journal of Advances in Medicine, 2021)
Background: Deficiency of magnesium is common and often ignored. It is associated with cardiac irregularity, cardiac insufficiency, seizure and electrolyte imbalance. As this element has multiple functions in our body it is important in the pathophysiology of several critical illnesses in intensive care unit (ICU). Hence the present study was undertaken to determine the usefulness of admission serum magnesium levels with regards to patient outcome considering mortality, need and duration of ventilator support, and acute physiologic assessment and chronic health evaluation 2 (APACHE 2) score. Methods: Demographic data such as age and sex were recorded. Patients were assessed for presenting complaints, history of other diseases and habits through an interview with the patients or care giver. These findings were recorded on a predesigned proforma patients was followed up for the outcomes such as mortality, need of ventilator support, duration of ICU stay and APACHE 2 score. Results: Regarding comparison between outcome of patients between two groups, 44% patients with magnesium level <1.7 mg/dl have improved and 72% patient didn’t improve. 44% patients with magnesium level >1.7 mg/dl have improved and 28% patient didn’t improve. Conclusions: From present observational study we can conclude that hypomagnesaemia is more common in patients more than 50 years of age and with male predominance. Pneumonia with septicaemia and cerebrovascular accident (CVA) was commonly associated with hypomagnesaemia. In present study we have observed that hypomagnesaemia is associated with high APACHE 2 score, poor outcome and more requirement of ventilatory support.